The impact of relative cohort size on U.S. fertility, 1913 - 2001 - Yongil Jeon; Michael P. Shields (Institute for the Study of Labor (IZA), 2008)
This paper tests for the long-term and short-term relationships between fertility and relative cohort size for the United States using the annual time series data between 1913 and 2001. An error correction model, imbedded with the cointegration theory, is coupled with the general impulse response function. Empirical evidence on relationships is found lending support to the Easterlin hypothesis in that the change in relative cohort size is an important explanatory variable to include in studies of human fertility both in the short run and in the long-run for the United States. In addition, our results support the catching-up hypothesis and that the child tax deduction has been an important policy variable influencing births.
urn:nbn:de:101:1-20080711124
Keywords: J13; 300; Easterlin hypothesis; relative cohort size; age structure; catching-up; child tax deduction; Fruchtbarkeit; Kohortenanalyse; Familienökonomik; Haushaltseinkommen; Familienleistungsausgleich; USA